Genetic variation in the growth hormone synthesis pathway in relation to circulating insulin-like growth factor-I, insulin-like growth factor binding protein-3, and breast cancer risk: results from the European prospective investigation into cancer and nutrition study. - Canzian, F; McKay, J; Cleveland, R; Dossus, L; Biessy, C; Boillot, C; Rinaldi, S; Llewellyn, M; Chajès, V; Clavel-Chapelon, F; Téhard, B; Chang-Claude, J; et al. (2005)
Insulin-like growth factor-I (IGF-I) stimulates cell proliferation and can enhance the development of tumors in different organs. Epidemiologic studies have shown that an elevated level of circulating IGF-I is associated to increased risk of breast cancer as well as other cancers. Genetic variants affecting the release or biological action of growth hormone (GH), the main stimulator of IGF-I production, may predict circulating levels of IGF-I and have an effect on cancer risk. We tested this hypothesis with a large case-control study of 807 breast cancer patients and 1,588 matched control subjects nested within the European Prospective Investigation into Cancer and Nutrition. We genotyped 22 common single nucleotide polymorphisms in 10 genes involved in GH production and action (GHRH, GHRHR, SST, SSTR1-SSTR5, POU1F1, and GH1), and in parallel, we measured serum levels of IGF-I and IGFBP-3, its major binding protein, in samples of cases and controls. SST and SSTR2 polymorphisms showed weak but statistically significant associations with breast cancer risk. SSTR5 polymorphisms were associated with IGF-I levels, whereas one polymorphism in GHRHR and one in POU1F1 were associated with IGFBP-3 levels. Our conclusion is that common genetic variation in the GH synthesis pathway, as measured by single nucleotide polymorphisms selected in the present study, is not a major determinant of IGF-I and IGFBP-3 circulating levels, and it does not play a major role in altering breast cancer risk.